2016
DOI: 10.1177/1528083716667259
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of alkali treatment condition on jute fabric for the development of rigid biocomposite

Abstract: Jute fiber has poor compatibility with hydrophobic thermosetting polymeric resin for the development of a biocomposite. In this present study, plain weave jute fabric was treated with 1% sodium hydroxide (owf) in three different time (30, 60 and 90 minutes), temperature (30, 40 and 50℃) and material-to-liquor ratio (1:5, 1:10 and 1:15) as per orthogonal array and the treated jute fabrics were used for the preparation of the biocomposite sheet by hand laying-cum-compression moulding method. Developed biocomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…The above ndings of the present study are further supported by the research work on jute bres; by combining the observation made by Roy et al (2012) and those of Lakshmanan et al (2016). Roy et al (2012) observed that the optimum treatment for producing a strong single Jute ber (610MPa) is 0.5% wt NaOH for 24h at ambient temperature, while Lakshmanan et al (2016) reported that the optimum treatment for producing a strong biocomposite (48.3MPa), with based matrix unsaturated polyester resin, using treated Jute bre is 1%w.t NaOH for 60min at 30°C.…”
Section: Ftir Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The above ndings of the present study are further supported by the research work on jute bres; by combining the observation made by Roy et al (2012) and those of Lakshmanan et al (2016). Roy et al (2012) observed that the optimum treatment for producing a strong single Jute ber (610MPa) is 0.5% wt NaOH for 24h at ambient temperature, while Lakshmanan et al (2016) reported that the optimum treatment for producing a strong biocomposite (48.3MPa), with based matrix unsaturated polyester resin, using treated Jute bre is 1%w.t NaOH for 60min at 30°C.…”
Section: Ftir Resultssupporting
confidence: 90%
“…Roy et al (2012) observed that the optimum treatment for producing a strong single Jute ber (610MPa) is 0.5% wt NaOH for 24h at ambient temperature, while Lakshmanan et al (2016) reported that the optimum treatment for producing a strong biocomposite (48.3MPa), with based matrix unsaturated polyester resin, using treated Jute bre is 1%w.t NaOH for 60min at 30°C. [17,18] It is thus observed, that a jute bre treated with a stronger alkaline solution, resulting in a lower tensile strength (25.7 %) but with better contact angle, will produce a stronger bre based composite.…”
Section: Ftir Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In FT, the slower decomposition rate, from 205 • C to 265 • C, shows gradual weight loss whereas the faster rate, from 265 • C to 360 • C, marks active pyrolysis. Maximum weight loss occurred at 325 • C for RT and WT jute fiber [25]. Active pyrolysis was lowest in the case of FT modified jute fiber.…”
Section: Thermo-gravimetric Analysis (Tga)mentioning
confidence: 93%
“…Sudha ve Thilagavathi, alkali işlemle birlikte jüt/vinilester kompozitlerinin basma dayanımı ve elektrik geçirgenliğinin arttığını belirtmişlerdir [13]. Benzer birçok çalışmada alkali işlemin jüt lifi takviyeli kompozitlerin mekanik ve yapısal özelliklerinde önemli iyileşmeler ortaya çıkardığı belirtilmiştir [14]- [18].…”
Section: Introductionunclassified